Language Variation in Print Media: A Study of Code Switching Patterns in Pakistani Urdu ‘Express’ Newspaper EditorialsLanguage Variation in Print Media: A Study of Code Switching Patterns in Pakistani Urdu ‘Express’ Newspaper Editorialshe Effects of Health Related Fitness Awareness on Physical Activity Among School Students (Journal of Asian Development Studies, 2026)
The current study explores the problematic background of language variation within the print media domain, specifically exploring code-switching patterns in the editorials of the Pakistani Urdu' Express' newspaper. Code-switching is a linguistic phenomenon involving alternation between two or more languages within a single discourse that reflects the dynamic interaction of cultural and communicative factors. The study put into practice a sociolinguistic lens to analyze the frequency, types, and functions of code-switching employed in the Urdu editorials of the 'Express' newspaper. The study applies a qualitative descriptive method; it produces descriptive data in the form of code-switched sentences from the editorial of Pakistani Urdu newspaper. 'Express' is selected for this purpose. One week of newspapers is collected for the current study from 1st October 2023 to 7th October 2023 to analyze code-switching in editorial sections. The analysis of data from the newspaper shows that the types of code-switching are intra-sentential, word code-switching, and total integrated Urdu. The most dominant type of code-switching observed is Intra-sentential (80%). The findings are expected to contribute to understanding how language is strategically employed in print media, shedding light on the role of code-switching as a tool for effective communication and cultural expression. This study holds significance in media discourse, as it exposes the linguistic choices made by writers and editors in the 'Express' newspaper, offering insights into the complex relationship between language, culture, and journalism. The results of this research are anticipated to inform future discussions on language dynamics within the Pakistani media landscape and contribute to the broader field of sociolinguistics.